2008
DOI: 10.1037/0022-006x.76.2.259
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of cognitive-behavioral treatment for posttraumatic stress disorder in severe mental illness.

Abstract: A cognitive-behavioral therapy (CBT) program for PTSD was developed to address its high prevalence in persons with severe mental illness receiving treatment at community mental health centers. CBT was compared to treatment as usual (TAU) in a randomized controlled trial with 108 clients with PTSD and either major mood disorder (85%) or schizophrenia or schizoaffective disorder (15%), of whom 25% also had borderline personality disorder. Eighty-one percent of clients assigned to CBT participated in the program.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
256
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(274 citation statements)
references
References 120 publications
9
256
0
8
Order By: Relevance
“…Psychoeducation and cognitive and behavioural strategies to reduce anxiety may be helpful (Frueh et al, 2009;Mueser et al, 2008). Exposure therapy and other specific therapies to address post-traumatic stress disorder in people with schizophrenia require further research before they can be recommended as treatments for schizophrenia.…”
Section: Traumamentioning
confidence: 99%
“…Psychoeducation and cognitive and behavioural strategies to reduce anxiety may be helpful (Frueh et al, 2009;Mueser et al, 2008). Exposure therapy and other specific therapies to address post-traumatic stress disorder in people with schizophrenia require further research before they can be recommended as treatments for schizophrenia.…”
Section: Traumamentioning
confidence: 99%
“…Separately, a study of cognitive-behavior psychotherapy (CBT) for PTSD among persons diagnosed with severe mental illness found psychotherapy superior to treatment as usual. CBT reduced PTSD symptoms and improved the patient's rating of the therapeutic alliance [81]. Further, a trial of CBT for schizophrenia failed to show a relationship between the subject's rating of therapeutic alliance and the therapist's questioning the rational basis for psychotic symptoms, a result that supports the conclusion that therapists can challenge a patient's false belief if a solid therapeutic relationship exists [82].…”
Section: General Principles For Managing Ptsd In Combat Veteran With Tbimentioning
confidence: 91%
“…In the second trial, 99 subjects were randomized to sertraline or placebo, and a statistically significant difference occurred for fewer depressive symptoms with sertraline at 12 weeks than with placebo [98]. One unique double-blind RCT compared sertraline, methylphenidate, and placebo [81]. Results from this trial showed a statistically significant decline in depressive symptoms with either sertraline or methylphenidate compared with placebo, but only when results were measured on the Hamilton Depression Rating Scale; no statistically significant improvement on Beck Depression Inventory scores occurred.…”
Section: Pharmacotherapy For Ptsd: Considerations For Comorbid Tbimentioning
confidence: 99%
“…[37] Birlikte bulunan bozukluklardan anksiyete bozuklukları kümesinde, özellikle de TSSB, yaygın anksiyete bozukluğu, OKB ve panik bozukluğun tedavisinde BDT'nin önemli başarı gösterdiği bilinmektedir. [25][26][27][28][29] Yine alkol bağımlılığı ve sınır kişilik bozukluğu eştanılarının bulunduğu durumlarında BDT'nin gelecek vaat ettiği düşünülmektedir. [29,30] Bununla birlikte bipolar bozukluğun akut döneminde manik atakta hem yeteri kadar çalışma yapılmamış, hem de BDT lehine önemli bir sonuç elde edilememiştir.…”
Section: Sonuçunclassified